Repairing and strengthening methods for RC structural members - Kocak, A.; Onal, M. M.; Sonmez, K. (TAYLOR & FRANCIS LTD, 2007)
In this study, the repairing and strengthening methods of reinforced columns and beams which are damaged during earthquakes have been compared. Due to earthquake and/or vertical loads, damaged or insufficient structural components can be repaired and strengthened with various methods. Reinforced jacketing, repairing with steel plates and repairing with FRP components are more used methods. We often come across these three methods in practise. These three methods have advantages and disadvantages. In this study, 21 beams were investigated experimentally The experimantal research is done on 6 reference beams and 6 cracked beams with its bottom U shaped reinforcements and by adding steel ropes to carrying points. Also 3 beams were retrofitted with steel plates on their tension zone and 6 beams were retrofitted by full jacketing. Strength degradation, energy dissipation, ductility and rigidity of the members using these methods given above are compared in the final section of this experimantal investigation.
Keywords: CONCRETE COLUMNS; BEAMS; SHEAR; Construction & Building Technology; Engineering